A flux-cored welding wire for repairing Mar-M247 defects and a preparation method and use method thereof

By using flux-core welding wire made of vacuum atomized alloy powder and inorganic powder, combined with the cold metal transition welding process, the liquefied crack problem caused by excessive welding heat input is solved, and the good combination of the weld and the base material is achieved and the efficient defect repair is achieved.

CN119237985BActive Publication Date: 2025-02-28DONGFANG TURBINE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411800097.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-28
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

When repairing defects of Mar-M247 high-temperature alloy, existing welding technology has the problem of liquefied cracks caused by excessive welding heat input, and lacks suitable welding materials.

Method used

Flux-core welding wire is used, which consists of vacuum atomized alloy powder and inorganic powder. The alloy powder includes elements such as Co, Cr, Al, Ti, Ta, Hf, Mo, Zr, W, C, etc., and is welded by cold metal transition welding process.

Benefits of technology

It effectively reduces the formation of thermal cracks, ensures the metallurgical combination of the weld and the base material, improves the uniformity and performance of the weld, and extends the service life of Mar-M247 alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention discloses a flux-cored welding wire for repairing defects of Mar‑M247, and a preparation method and a use method thereof. The flux-cored welding wire comprises a metal sheath and a filling powder coated therein, wherein the filling powder comprises a vacuum-atomized alloy powder and an inorganic powder, wherein the alloy powder comprises the following components: Co, Cr, Al, Ti, Ta, Hf, Mo, Zr, W, and C. The preparation method is used to prepare the above-mentioned flux-cored welding wire. The use method uses the above-mentioned flux-cored welding wire for welding. It can be used to repair defects of Mar‑M247 high-temperature alloy by fusion welding process; the alloy powder containing high melting point elements is mixed uniformly by vacuum atomization powder making in advance to avoid the problem of insufficient metallurgical reaction of high melting point single metal in low heat input mode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloy crack repair, in particular to a flux-cored welding wire for repairing Mar-M247 defects and a preparation method and a use method thereof. Background Art

[0002] Mar-M247 nickel-based superalloy was designed in the 1970s. It is a typical polycrystalline precipitation-strengthened nickel-based superalloy. It is mainly produced by casting or directional solidification. It is a key material for manufacturing gas turbines, aircraft engine blades and other operating system components. It is currently widely used. Under standard heat treatment process, 62% of the strengthening phase γ'[Ni3(Al,Ti)] is precipitated in Mar-M247, which is orderly distributed in the matrix phase γ. There is a certain content (less than 13.5%) of refractory elements (Ta, Hf, W, Mo) in Mar-M247. Some refractory elements such as Hf, Ta, W, Zr and C form carbides and precipitate at the grain boundaries. The presence of γ' and carbides makes Mar-M247 exhibit excellent thermomechanical properties at high temperatures, can ensure good creep and fatigue properties under repeated impact, and has high oxidation resistance and corrosion resistance, and presents reliable thermal stability as a whole. Components made of Mar-M247 material will develop defects such as cracks after serving in harsh working conditions. How to repair the defects and extend the service life through remanufacturing technology is an urgent problem that needs to be solved.

[0003] However, this material contains a high content of alloying elements such as Al and Ti, and has a high tendency to thermal cracks, which brings great difficulties to remanufacturing. The repair processes that have been used include brazing and thermal spraying, but the bonding strength is not high enough, and the hot isostatic pressing process is limited in the size of the workpiece. Transient liquid phase joining (TLP), as a low heat input joining process, is considered to be the best method for joining nickel-based alloys and can achieve crack-free joining of Mar-m247. However, TLP joining usually has certain requirements on the defect shape and requires long-term diffusion and homogenization treatment. The complex process limits its actual engineering application in repair. The most commonly used welding methods have two main problems. One is that the welding heat source generally has a large welding heat input, which makes it difficult to cause liquefaction cracks in the welding heat affected zone. On the other hand, there is no welding material suitable for M247. For the problem of excessive welding heat input, the recently developed low heat input welding technology has partially solved the problem of liquefaction cracks, such as the cold metal transfer welding (CMT) process, but the lack of corresponding matching welding materials has always been another major constraint restricting the use of welding methods to repair Mar-M247. Summary of the invention

[0004] The object of the present invention is to provide a flux-cored welding wire for repairing Mar-M247 defects and a preparation method and a use method thereof in order to solve the above-mentioned problem of weld metal solidification cracks.

[0005] The technical solution adopted by the present invention is as follows:

[0006] A flux-cored welding wire for repairing Mar-M247 defects comprises: a metal outer skin and a filling powder coated therein, wherein the filling powder comprises a vacuum atomized alloy powder and an inorganic powder, and the alloy powder comprises the following components: Co, Cr, Al, Ti, Ta, Hf, Mo, Zr, W, and C.

[0007] Optionally, the metal outer skin is pure nickel skin.

[0008] Optionally, the alloy powder includes the following components (accounting for the weight ratio of the alloy powder): Co: 5~12%, Cr: 3~10%, Al: 3~7%, Ti: 0.5~4%, Ta: 1~4%, Hf: 0.5~2%, Mo: 0.2~1%, Zr: 0.01~0.5%, W: 2~12%, C: 0.1~0.3%, and the balance is Ni.

[0009] Optionally, the inorganic powder includes the following components (based on the weight of the filling powder): YSZ: 0.1-1%, quartz: 1-4%, rutile: 2-10%, ferrotitanium: 5-10%, and the remainder is alloy powder.

[0010] Optionally, the filling powder has a particle size of 50-110 μm.

[0011] A method for preparing a flux-cored welding wire for repairing Mar-M247 defects comprises the following steps:

[0012] Step 1, mixing alloy powders, wherein the alloy powders contain the following components (by weight of the alloy powders): Co: 5-12%, Cr: 3-10%, Al: 3-7%, Ti: 0.5-4%, Ta: 1-4%, Hf: 0.5-2%, Mo: 0.2-1%, Zr: 0.01-0.5%, W: 2-12%, C: 0.1-0.3%, and the balance is Ni, melting the mixture into a liquid state in a vacuum smelting furnace, and then preparing a spherical powder by a vacuum mist method;

[0013] Step 2, adding the powder obtained by vacuum atomization to inorganic powder to obtain filling powder, wherein the inorganic powder comprises the following components (accounting for the weight ratio of the filling powder): YSZ: 0.1-1%, quartz: 1-4%, rutile: 2-10%, ferrotitanium: 5-10%, and the balance is alloy powder;

[0014] Step 3: The filling powder obtained in the above step 2 is coated with pure nickel skin, and the powder is continuously reduced and drawn to obtain a flux-cored welding wire for repairing Mar-M247 alloy.

[0015] Optionally, step 3 includes the following steps:

[0016] Step 3.1, rolling the pure nickel skin into a U-shaped cross-section shape;

[0017] Step 3.2, adding the filling powder prepared according to the dosage into the U-shaped pure nickel skin;

[0018] Step 3.3: After the filling powder is filled, use a rolling mill to compact the pure nickel skin and the filling powder to ensure that the filling powder is evenly distributed;

[0019] Step 3.4: The welding wire is made into flux-cored welding wires of different specifications through a drawing process.

[0020] A method for using a flux-cored welding wire for repairing Mar-M247 defects, using the flux-cored welding wire as described above, adopting a cold metal transition welding process for welding, keeping the welding gun and the substrate at 90 degrees and a distance of 15-20 mm during the welding process; using high-purity argon as the shielding gas, with a gas flow rate of 15-20 L / min. The welding current is 80-120 A, the welding voltage is 10-14 V, the wire feeding speed is 2.0-4.8 m / min, and the welding speed is 0.3-0.4 m / min.

[0021] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0022] 1. The flux-cored welding wire for repairing Mar-M247 defects provided by the present invention has a composition and performance close to that of the base material, and is added with a substance that inhibits thermal cracks, and can be used for repairing the defects of Mar-M247 high-temperature alloy by fusion welding process; the alloy powder containing high melting point elements is mixed in advance by vacuum atomization to avoid the problem of insufficient metallurgical reaction of high melting point single metal under low heat input mode.

[0023] 2. The flux-cored welding wire for repairing Mar-M247 defects provided by the present invention is added with a small amount of YSZ, which can effectively refine the grains by arc metallurgical reaction, reduce the continuous distribution of low-melting-point eutectics between grains, and inhibit the generation of thermal cracks; titanium iron serves as an effective deoxidizer, which can fully deoxidize the welding molten pool, and form slag with quartz, rutile, etc. to cover the molten pool, thereby reducing the oxygen content of the cladding metal and oxide inclusions. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The present invention will now be described by way of example with reference to the accompanying drawings, in which:

[0025] Figure 1This is the morphology of the cladding layer in Example 1.

[0026] Figure 2 This is the second morphology of the cladding layer in the embodiment.

[0027] Figure 3 This is the morphology of the cladding layer in Example 3.

[0028] Figure 4 This is the morphology of the cladding layer in Example 4. DETAILED DESCRIPTION

[0029] The present invention will be described in detail below in conjunction with the accompanying drawings.

[0030] All features disclosed in this specification, or steps in all methods or processes disclosed, except mutually exclusive features and / or steps, can be combined in any manner.

[0031] Any feature disclosed in this specification, unless otherwise stated, can be replaced by other equivalent or alternative features with similar purposes. That is, unless otherwise stated, each feature is only an example of a series of equivalent or similar features.

[0032] A flux-cored welding wire for repairing Mar-M247 defects, a preparation method thereof and a use method thereof, comprising: a metal outer skin and a filling powder coated therein, wherein the filling powder comprises a vacuum atomized alloy powder and an inorganic powder, and the alloy powder comprises the following components (in weight ratio of the filling powder): Co: 5-12%, Cr: 3-10%, Al: 3-7%, Ti: 0.5-4%, Ta: 1-4%, Hf: 0.5-2%, Mo: 0.2-1%, Zr: 0.01-0.5%, W: 2-12%, and C: 0.1-0.3%.

[0033] Specifically, flux-cored wire can provide better heat input control in CMT welding process, help reduce the formation of hot cracks, and allow precise control of the alloy composition of the weld to match the performance of Mar-M247 alloy. In addition, the flux-cored wire coating will melt and release protective gas and slag during welding, which can protect the molten pool from air pollution. Among them, the composition of the alloy powder is similar to that of Mar-M247 alloy, which can ensure the metallurgical bonding of the weld and the base material. In particular, Mar-M247 contains refractory metal materials with high melting points. When using low heat input welding process, it is likely that the metallurgical reaction of the molten pool is not sufficient. The high melting point metal powder may not be completely melted during the welding process, resulting in unmelted solid particles in the weld, affecting the uniformity and performance of the weld. In this scheme, vacuum atomized alloy powder is used, and the metal powder has uniform particle size, which helps the uniform melting and solidification of the weld metal, and has a high chemical purity, reduces impurities in the weld, and improves the quality of the weld. And the surface characteristics of vacuum atomized powder help to improve the wettability of powder and molten pool metal, thereby obtaining better weld formation.

[0034] As another specific embodiment, the metal outer skin is pure nickel skin. The melting point of pure nickel skin matches that of Mar-M247 alloy, which can ensure that the welding wire and the base material melt synchronously during welding, and can reduce the dilution effect of the filler metal on the Mar-M247 alloy, thereby maintaining the chemical composition of the weld stable.

[0035] As another specific embodiment, the alloy powder includes the following components (accounting for the weight ratio of the alloy powder): Co: 5~12%, Cr: 3~10%, Al: 3~7%, Ti: 0.5~4%, Ta: 1~4%, Hf: 0.5~2%, Mo: 0.2~1%, Zr: 0.01~0.5%, W: 2~12%, C: 0.1~0.3%, and the balance is Ni. The above element combination can produce a composite effect in the alloy, improving the high temperature strength, corrosion resistance, heat resistance and oxidation resistance of the alloy. Among them, Co can enhance the high temperature strength and corrosion resistance of the alloy, Cr can improve the corrosion resistance and oxidation resistance of the alloy, Al can improve the strength and corrosion resistance of the alloy, Ti and Ta can improve the plasticity and toughness of the alloy, and improve the tensile and compression resistance of the alloy. High contents of Cr, Al, Ti and Ta and other elements enhance the oxidation resistance and corrosion resistance of the weld at high temperatures. In addition, adding Hf, Mo, Zr and other elements can improve the high temperature strength and corrosion resistance of the alloy, inhibit grain boundary growth, and improve the grain boundary bonding ability of the alloy. W can increase the melting point and high temperature strength of the weld and increase the wear resistance of the weld. C improves the strength and controls the microstructure of the weld, and this ratio does not lead to a decrease in toughness. The composition ratio of the alloy powder optimizes the strength, hardness, toughness and high temperature performance of the weld to match the Mar-M247 alloy.

[0036] As another specific embodiment, the inorganic powder includes the following components (by weight of the filling powder): YSZ: 0.1-1%, quartz: 1-4%, rutile: 2-10%, ferrotitanium: 5-10%, and the balance is alloy powder. The addition of inorganic substances can enhance the compactness, hardness and heat resistance of the filling layer. Among them, YSZ (stabilized zirconia) has good high temperature stability and chemical stability, which can improve the hardness and wear resistance of the filling layer; quartz can increase the resistance of the filling layer to thermal shock and temperature changes; rutile can improve the protective layer of the filling layer to prevent oxidation reaction between the filling layer and the substrate; ferrotitanium can enhance the resistance of the filling layer to the external environment, making it more stable and reliable.

[0037] As another specific embodiment, the powder particle size of the filler powder is 50-110 μm. The filler powder can be quickly melted and evenly transported to the welding area, which helps to form a uniform weld. Too coarse powder may cause a rough weld surface, and too fine powder may cause pores or other defects inside the weld, while this solution helps to form a smooth weld surface.

[0038] A method for preparing a flux-cored welding wire for repairing Mar-M247 defects comprises the following steps:

[0039] Step 1: Mix the alloy powders, wherein the alloy powders contain the following components (by weight): Co: 5-12%, Cr: 3-10%, Al: 3-7%, Ti: 0.5-4%, Ta: 1-4%, Hf: 0.5-2%, Mo: 0.2-1%, Zr: 0.01-0.5%, W: 2-12%, C: 0.1-0.3%, and the balance is Ni. The mixture is melted into a liquid state in a vacuum smelting furnace, and then prepared into a spherical powder by a vacuum atomization method. The elements (Co, Cr, Al, Ti, Ta, Hf, Mo, Zr, W, C) contained in the alloy powder can ensure that the weld metal has mechanical properties and heat resistance similar to or improved from those of Mar-M247 alloy. Melting the mixture in a vacuum smelting furnace can obtain a high-purity alloy. Vacuum atomizing the liquid alloy into a spherical powder can obtain a powder that is easy to melt, has good fluidity and welding processability.

[0040] Step 2: Add the powder obtained by vacuum atomization to inorganic powder to obtain filling powder, wherein the inorganic powder includes the following components (accounting for the weight ratio of filling powder): YSZ: 0.1~1%, quartz: 1~4%, rutile: 2~10%, ferrotitanium: 5~10%, and the balance is alloy powder, and the balance is alloy powder; adding inorganic powders such as YSZ, quartz, rutile and ferrotitanium to the alloy powder can effectively refine the grains and reduce the oxygen content and oxide inclusions of the cladding metal. Among them, vacuum atomization of the alloy powder first can ensure the purity of the alloy powder, reduce the content of impurities such as oxygen and nitrogen, and can accurately control the particle size of the powder. If the alloy powder and the inorganic powder are mixed and then vacuum atomized, the particle size distribution may be uneven due to the differences in melting points and fluidity of different substances, affecting the welding effect.

[0041] Step 3: Use pure nickel to coat the filling powder obtained in step 2 above, and then continuously reduce the diameter of the powder to obtain a flux-cored welding wire for repairing Mar-M247 alloy. This can protect the internal powder from contamination and provide a shell that is easily melted during welding, thereby ensuring that the powder can be smoothly fed into the welding area. Continuous reduction and drawing can ensure that the welding wire has a uniform diameter and structure, and the coated powder is made into a flux-cored welding wire with a certain size and shape.

[0042] As another specific implementation, the step 3 includes the following steps:

[0043] Step 3.1, rolling the pure nickel skin into a U-shaped cross-section shape; the U-shaped structure helps to fill and seal the powder more easily in the subsequent steps.

[0044] Step 3.2: Add the dosed filler powder into the U-shaped pure nickel skin; this ensures that the chemical composition of the welding wire is uniform, thereby obtaining consistent weld characteristics during the welding process.

[0045] Step 3.3: After the filling powder is filled, use a rolling mill to compact the pure nickel skin and the filling powder to ensure that the filling powder is evenly distributed; ensure that the pure nickel skin tightly wraps the filling powder to prevent the powder from moving or falling off during drawing and transportation.

[0046] Step 3.4: The welding wire is made into flux-cored welding wire of different specifications through a drawing process; it is used to reduce the diameter of the welding wire to reach the required specifications, while further compacting the filling powder to improve the strength and uniformity of the welding wire.

[0047] A method for using a flux-cored welding wire for repairing Mar-M247 defects, using the flux-cored welding wire as described above, adopting a cold metal transition welding process for welding, keeping the welding gun and the substrate at 90 degrees and a distance of 15-20 mm during the welding process; using high-purity argon as the shielding gas, with a gas flow rate of 15-20 L / min. The welding current is 80-120 A, the welding voltage is 10-14 V, the wire feeding speed is 2.0-4.8 m / min, and the welding speed is 0.3-0.4 m / min.

[0048] Example

[0049] A method for preparing a flux-cored welding wire for repairing Mar-M247 defects, step 1, mixing alloy powders, wherein the alloy powders contain the following components (accounting for the weight ratio of the alloy powders): Co: 8%, Cr: 6%, Al: 5%, Ti: 1%, Ta: 2%, Hf: 1.5%, Mo: 1%, Zr: 0.3%, W: 8%, WC: 2%, and the balance is Ni. The above mixture is melted into a liquid state in a vacuum smelting furnace, and then prepared into a spherical powder by a vacuum atomization method. As the metal powder for filling the flux-cored welding wire, the optimized powder particle size is 50-110μm;

[0050] Step 2: Add the powder obtained by vacuum atomization to inorganic powder to obtain filling powder, and mix them thoroughly using a powder mixer. The inorganic powder includes the following components (by weight of the filling powder): YSZ: 0.5%, quartz: 2%, rutile: 5%, ferrotitanium: 5%, and the balance is the above alloy powder; the optimized powder particle size suitable for the preparation of flux-cored welding wire is 50-110 μm.

[0051] Step 3

[0052] Step 3.1, select pure nickel skin with a thickness of 0.2 mm and a width of 8 mm as the metal outer skin of the flux-cored welding wire, and roll the pure nickel skin into a U-shaped cross-section shape;

[0053] Step 3.2, adding the filling powder prepared according to the dosage into the U-shaped pure nickel skin;

[0054] Step 3.3: After the filling powder is filled, use a rolling mill to compact the pure nickel skin and the filling powder to ensure that the filling powder is evenly distributed;

[0055] Step 3.4: The welding wire is made into a 1.2 mm flux-cored welding wire through a drawing process.

[0056] A method for using a flux-cored welding wire for repairing Mar-M247 defects,

[0057] The welding was performed using the TransPuls Synergic 5000 CMT welding system from Fronius. During the welding process, the welding gun was kept at 90° and 15 mm from the substrate. High-purity argon was used as the shielding gas with a gas flow rate of 20 L / min. The welding current was 80-120 A, the welding voltage was 10-14 V, the wire feed speed was 2.0-4.8 m / min, and the welding speed was 0.3 m / min.

[0058] Four embodiments are given below according to different wire feeding speeds, welding currents and welding voltages, and the relevant parameters are shown in Table 1:

[0059] Table 1 Process parameters of CMT repair welding

[0060]

[0061] The EDS composition analysis of the cladding layer obtained is shown in Table 2:

[0062] Table 2 EDS analysis results of chemical composition of cladding layer

[0063]

[0064] The morphology of the cladding layer obtained under different parameters is as follows: Figure 1-4 As shown in Figure 2, when the welding current is below 120A, no thermal cracks appear in the weld and heat-affected zone (such as Figure 1-Figure 3 As shown in the figure), when the A value exceeds 120A, thermal cracks appear in the heat-affected zone of the base material, and no weld appears (as shown in the figure). Figure 4 However, when the welding current is lower than 80A, due to the solidification of the cladding metal, process pores appear in the weld (such as Figure 1 as shown).

[0065] The present invention is not limited to the above-mentioned specific embodiments, but extends to any new features or any new combination disclosed in this specification, as well as any new method or process steps or any new combination disclosed.

Claims

1. A flux-cored welding wire for repairing Mar-M247 defects, characterized in that: include: A metal outer skin and a filling powder coated therein, wherein the filling powder comprises a vacuum atomized alloy powder or an inorganic powder; The metal outer skin is pure nickel skin; The alloy powder comprises the following components by weight of the alloy powder: Co: 5-12%, Cr: 3-10%, Al: 3-7%, Ti: 0.5-4%, Ta: 1-4%, Hf: 0.5-2%, Mo: 0.2-1%, Zr: 0.01-0.5%, W: 2-12%, C: 0.1-0.3%, and the balance is Ni; The inorganic powder includes the following components in weight ratio of the filling powder: YSZ: 0.1-1%, quartz: 1-4%, rutile: 2-10%, titanium iron: 5-10%, and the balance is alloy powder.

2. The flux-cored welding wire for repairing Mar-M247 defects according to claim 1, characterized in that: The filling powder has a particle size of 50-110 μm.

3. A method for preparing a flux-cored welding wire for repairing Mar-M247 defects, characterized in that: The following steps are involved: Step 1, mixing alloy powders, wherein the alloy powders contain the following components by weight: Co: 5-12%, Cr: 3-10%, Al: 3-7%, Ti: 0.5-4%, Ta: 1-4%, Hf: 0.5-2%, Mo: 0.2-1%, Zr: 0.01-0.5%, W: 2-12%, C: 0.1-0.3%, and the balance is Ni, melting the mixture into a liquid state in a vacuum smelting furnace, and then preparing a spherical powder by a vacuum mist method; Step 2, adding the powder obtained by vacuum atomization to inorganic powder to obtain filling powder, wherein the inorganic powder includes the following components by weight of the filling powder: YSZ: 0.1-1%, quartz: 1-4%, rutile: 2-10%, ferrotitanium: 5-10%, and the balance is alloy powder; Step 3: The filling powder obtained in the above step 2 is coated with pure nickel skin, and the powder is continuously reduced and drawn to obtain a flux-cored welding wire for repairing Mar-M247 alloy.

4. The method for preparing a flux-cored welding wire for repairing Mar-M247 defects according to claim 3, characterized in that: The step 3 comprises the following steps: Step 3.1, rolling the pure nickel skin into a U-shaped cross-section shape; Step 3.2, adding the filling powder prepared according to the dosage into the U-shaped pure nickel skin; Step 3.3: After the filling powder is filled, use a rolling mill to compact the pure nickel skin and the filling powder to ensure that the filling powder is evenly distributed; Step 3.4: The welding wire is made into flux-cored welding wires of different specifications through a drawing process.

5. A method for using a flux-cored welding wire for repairing Mar-M247 defects, using the flux-cored welding wire as claimed in claim 1 or 2, characterized in that: The cold metal transfer welding process is used for welding. During the welding process, the welding gun is kept at 90° to the substrate and the distance is 15-20mm. High-purity argon is used as the shielding gas with a gas flow rate of 15-20L / min. The welding current is 80-120A, the welding voltage is 10-14V, the wire feeding speed is 2.0-4.8m / min, and the welding speed is 0.3-0.4m / min.

Citation Information

Patent Citations

  • Method of cladding and fusion welding of superalloys

    US20180257181A1

  • Low-nickel Nitrogen-containing Austenitic Stainless Steel Flux-cored Wire and Preparation Method Thereof

    US20210252648A1